Voltage-based Device Tracking in a 1.5 Tesla MRI during Imaging: Initial validation in swine models - Schmidt, Ehud J (2014)
PURPOSE: Voltage-based device-tracking (VDT) systems are commonly used for tracking invasive devices in electrophysiological (EP) cardiac-arrhythmia therapy. During EP procedures, electro-anatomic-mapping (EAM) workstations provide guidance by integrating VDT location and intra-cardiac-ECG information with X-ray, CT, Ultrasound, and MR images. MR assists navigation, mapping and radio-frequency-ablation. Multi-modality interventions require multiple patient transfers between an MRI and the X-ray/ultrasound EP suite, increasing the likelihood of patient-motion and image mis-registration. An MRI-compatible VDT system may increase efficiency, since there is currently no single method to track devices both inside and outside the MRI scanner. METHODS: An MRI-compatible VDT system was constructed by modifying a commercial system. Hardware was added to reduce MRI gradient-ramp and radio-frequency-unblanking-pulse interference. VDT patches and cables were modified to reduce heating. Five swine cardiac VDT EAM-mapping interventions were performed, navigating inside and thereafter outside the MRI. RESULTS: Three-catheter VDT interventions were performed at >12 frames-per-second both inside and outside the MRI scanner with <3mm error. Catheters were followed on VDT- and MRI-derived maps. Simultaneous VDT and imaging was possible in repetition-time (TR) >32 msec sequences with <0.5mm errors, and <5% MRI SNR loss. At shorter TRs, only intra-cardiac-ECG was reliable. RF Heating was <1.5C°. CONCLUSION: An MRI-compatible VDT system is feasible.